Membangun kedaulatan negara melalui pendekatan geostrategi dan geopolitik - salsabila, adelia putri (Maliki Interdisciplinary Journal, 2026)
This paper examines the crucial role of geopolitical and geostrategic strategies in supporting national sovereignty, particularly in a global context, where they serve as the foundation for maintaining territorial integrity, social identity, sustainability, and multidimensional challenges such as the energy crisis, technological disruption, and great power rivalry. The primary issue raised is how a state can formulate a geostrategic and geopolitical approach as a crucial safeguard in understanding its geographic position, resource potential, and internal and external threats that impact national stability. Through the correct application of geostrategy, a state can optimize regional strength, strengthen defenses, and build comprehensive national resilience. Geopolitics, meanwhile, plays a role in formulating policies aligned with geographic conditions and national interests. Romi Faslah once explained that geostrategy and geopolitics are inseparable in shaping a strong national policy direction. (Faslah, 2024) The study's findings demonstrate that geopolitical and geostrategic strategies designed with national identity and the global context in mind can serve as a key foundation for strengthening a state's resilience to external pressures and internal crises. Therefore, synergy between the state, civil society, and the private sector is necessary to build adaptive sovereignty and sustainable development.